PERSEPSI MAHASISWA TERHADAP KUALITAS LAYANAN STAF ADMINISTRASI DAN TEKNISI JURUSAN PADA LEMBAGA PENDIDIKAN TINGGI NEGERI DI KOTA PONTIANAK - Herdiansyah, Dedi; Wahyuarini, Tri; Elida, Sri Syabanita; Novieyana, Syarifah (PRESTASI, 2014)
AbstractÂ The winner in business competition is organization which provides the best quality service for its customers. The purpose of this study is to confirm the effect of quality service on studentsâ satisfaction of a higher educational institution in Pontianak. There are four dimension of SERVQUAL that covers in this research, namely: tangibles, reliability, responsiveness and emphaty. Service quality was represented by four administrative and technician staff that frequently handle studentsâ problems. Survey was used as data collection method while questionnaire was used as data collection tool. Samples were chosen by probability sampling, stratified random sampling. Result of the study showed an affect of the four dimensions of SERVQUAL on studentsâ satisfaction, where the most significant effect was occur from emphaty dimension.Â Keywords: quality service, customer satisfaction, administrative, technician and staff.